Adoption of Climate-Smart Agriculture (CSA) in Flood-Affected Regions of Darbhanga - Shankar Mishra, Jay; Doharey, R K; Meena, N R; Sonu, Kumar; Deekshith, Bachali (Indian Journal of Extension Education, 2025)
The study aimed to evaluate the extent of adoption of Climate Smart Agriculture (CSA) practices among farmers residing in flood-prone areas of Darbhanga, Bihar, and to identify the key socio-economic factors influencing adoption. Data were collected during 2024– 2025 from 160 respondents randomly selected from sixteen villages across four flood affected blocks. A pre-tested interview schedule encompassing five CSA components was employed to gather information on adoption levels and socio-economic characteristics. The adoption of CSA practices was predominantly partial and practice-specific. Crop production practices recorded mean adoption rate of 49.51 per cent, whereas smart water management at 38.37 per cent. Overall, 64.16 per cent of the respondents exhibited a moderate adoption level. Correlation analysis demonstrated significant positive associations between adoption and variables such as knowledge, income, education, and family size. Further, the regression model (R² = 0.500; F = 13.451; p < 0.01) identified knowledge, income, education, family size, and extension contact as significant predictors of CSA adoption. The study concluded that improving farmers’ knowledge and enhancing their economic capacity could substantially increase CSA adoption, thereby strengthening climate resilience. These results underscore the importance of targeted extension services and capacity-building programs tailored to vulnerable regions.
Keywords: CSA adoption; Flood-prone; Climate-smart practices; Regression; Bihar